Analisis Data Hasil Pengujian Multilokasi Padi Sawah dengan Menggunakan Model AMMI - Idris, Idris (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2015)
Various study of multi-location test of rice genotypes was strongly influenced by field and environmental factors. This study aimed to implement and to identify wetland rice genotypes. Multi-location test was conducted on some rice genotypes in Southeast Sulawesi in 2010 at various locations. Randomized block design was used with three replications in different locations. Data were analyzed using AMMI model. Results showed that rice production had the main effect with the genotype of KUI 1 and KUI 2. Moreover, BIPLOT test found that the genotype 2 of S3393-2F-17-1-1 was the only one of unstable genotype, and the rest were stable genotype. Not surprisingly, genotype (G) 4 (S3382-2D-PN-4-1), G 5 (S3382-2D-PN-6-3-3), G 7 (S3382-2D-PN-2D-1-1), G 11 (S3382-2D-1-1), G13 (Ciherang) and G 14 (Cisantana) were relatively stable. Those genotypes could be recommended as the high potential yield due to higher average production compared with general average. This study also indicated that G 3 (S3381-2D-PN-27-2), G 9 (S4359-E-11-2), and G 12 (IR64) are very suitable for growing in location A at Ladongi. Moreover, in location B study suggested that G 11 (OBS-9595) should be recommended at Wundulako. Finally, in Lambuya, particularly in location C, study indicated that some genotypes can grow well, viz. G 6 (S3382-2D-PN-17-3), G 8 (S4690 G-KN-4-3) and G 14 (Cisantana).